(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
This study focuses on the traditionally used plants and fungi in the Berd region of Armenia, which is the eastern section of the Ijevan floristic district. Field studies were conducted during the vegetation periods from 2017 to 2025. In this region, we identified 515 species of vascular plants belonging to 95 families and 321 genera that have some use. The useful plants account for about 61% of the flora species found in the Berd region. The recorded species included 389 medicinal plants, 204 wild edible species, 194 species of ornamental plants, 13 species used of wood, and 66 species of plant dyes. About 160 species have high forage value, 17 species are insecticidal plants, and 201 are considered honey plants. It should be noted that we have marked 58 species as poisonous, some of which also have medicinal uses. About 200 species of edible mushrooms were found in the studied area, of which 18 species are the most commonly used by the population. Local communities have some knowledge about these macrofungi, which play a substantial role in their survival. There are also 45 species of poisonous mushrooms and 60 species with medicinal properties. During multiple visits, we conducted interviews with the local population. We studied all 16 villages in the region and interviewed 317 local people. Approximately 41% of the useful species growing in the Berd region were not reported by local people during their interviews. On the other hand, some of the species used in this region aren’t considered edible by the people of Central Armenia. Ethnobotany and indigenous knowledge contribute to the sustainable development and education of the population on a national scale, without losing ethnic characteristics and traditions. Our investigation is not only about cataloging plant and fungal uses but also biodiversity conservation and understanding the cultural meanings, and worldviews that shape the human-nature relationship, which nowadays are often threatened by globalisation.